Web application development with R using Shiny : build stunning graphics and interactive data visualizations to deliver cutting-edge analytics /: build stunning graphics and interactive data visualizations to deliver cutting-edge analytics. (2018) - Beeley, Chris; Sukhdeve, Shitalkumar R
No abstract available